Protein import into chloroplasts - Vothknecht, Ute (Henry Stewart Talks, 2007)
The endosymbiotic origin of chloroplasts, Protein import as a result of genome rearrangements, Different targeting pathways, The general import pathway, Properties of the targeting process, Cytosolic components, Components of the Toc and Tic translocon, Stromal components, Phylogenetic origin of the import apparatus